miR-223: An Immune Regulator in Infectious Disorders - Yuan, Shun; Wu, Qi; Wang, Zhiwei; Che, Yanjia; Zheng, Sihao; Chen, Yuanyang; Zhong, Xiaohan; Shi, Feng (Frontiers in Immunology, 2021)
MicroRNAs (miRNAs) are small, single-stranded non-coding RNAs that can influence disease development and progression by post-transcriptionally regulating the expression of genes encoding proteins. MiR-223 was first identified as a regulator of hematopoietic lineage differentiation in 2003. As anti-inflammatory miRNA, miR-223 exhibits multiple regulatory functions in immune response, and abnormal expression of miR-223 has been demonstrated to be involved in multiple types infectious inflammatory diseases, including viral hepatitis, human immunodeficiency virus type 1 (HIV-1), tuberculosis (TB), via influencing neutrophil infiltration, macrophage function, dendritic cells (DCs) maturation and inflammasome activation. This review first provides a systematic overview of the current knowledge of the physiopathology of miR-223, and then highlights molecular mechanisms of miR-223 in infectious diseases and its potential applications as biomarkers for early diagnosis and therapeutic target against infectious diseases.